Dois ensaios sobre a desigualdade de renda dos municipios brasileiros - Rodrigo Lara Pinto Coelho (2006)
The role of initial conditions in establishing the long-term income levels of the economies, and, consequently, over inequality is a subject which remains in active debate. To this end, the first paper attempts to ascertain which of the convergence hypotheses absolute, conditional or club best describes the dynamics of the Brazilian municipalities income over the period 1970-2000. The results based on the regression tree method and on robustness tests demonstrate the importance of initial conditions on the determination of municipalities income growth rate, which suggests the dominance of the club convergence hypothesis over the other two.Having as a starting point these results and the empirical finding that the income of the Brazilian municipalities has moved toward a two-peaked distribution between 1970 and 2000, the second paper attempts to identify among the set of variables capital-output ratio, human capital per worker and total factor productivity, possible sources of the so called development trap. The analysis of each of these variables conducted based on a combination of nonparametric methods and clustering algorithms points to the human capital as the main responsible for the bimodal shape of the Brazilian municipalities income distribution.